Website Edukasi untuk Perubahan Pengetahuan dan Perilaku Defensive Driving Operator Head Truck - Washul, Muhammad; Widjanarti, Maria Paskanita; Fauzi, Rachmawati Prihantina (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
The operational activity of unloading and loading packaging at PT X Semarang involves the performance of operators who drive the head truck and chassis. The operators were poorly knowledgeable and behaved towards defensive driving. This study aimed to analyze the effectiveness of the Defensive Driving Site or “Devise” educational website to improve head truck operators’ defensive driving knowledge and behavior. The design of this study was pre-test and post-test with control group. The respondents of the study were 106 head truck operators of PT X Semarang, with the intervention and control groups consisting of 53 respondents each. Before and after the intervention measurements of defensive driving knowledge and behavior were conducted. Comparison of the results between the two groups was analyzed by t -test. The results of the study showed that the p-value for the comparison of knowledge about defensive driving in the intervention group that received an educational website was 0.001 (there was a meaningful difference). The p value for the comparison of defensive driving behavior in the intervention group was 0.001 (there was a meaningful difference). The p-value for the comparison of knowledge about defensive driving in the control group was 0.146 (no meaningful difference). The p-value for the comparison of defensive driving behavior in the control group was 0.226 (no meaningful difference). There was a difference in defensive driving knowledge (p = 0.001) and a difference in defensive driving behavior (p = 0.001) between the intervention group and the control group. It was further concluded that the educational website was successful in improving the knowledge and defensive driving behavior of PT X Semarang head truck operators.Keywords: educational website; defensive driving; knowledge; behavior; operator head truck ABSTRAK Aktivitas operasional bongkar-muat peti kemas di PT X Semarang melibatkan kinerja operator yang mengendarai head truck dan chassis. Para operator berpengetahuan dan berperilaku kurang baik terhadap defensive driving. Penelitian ini bertujuan untuk menganalisis efektivitas website edukasi Defensive Driving Site atau “Devise” untuk meningkatkan pengetahuan dan perilaku defensive driving operator head truck. Desain penelitian ini adalah pre-test and post-test with control group. Responden penelitian adalah 106 operator head truck PT X Semarang, dengan kelompok intervensi dan kontrol masing-masing terdiri atas 53 responden. Sebelum dan sesudah intervensi dilakukan pengukuran pengetahuan dan perilaku defensive driving. Perbandingan hasil antara kedua kelompok dianalisis dengan uji t. Hasil penelitian menunjukkan bahwa nilai p untuk perbandingan pengetahuan tentang defensive driving pada kelompok intervensi yang mendapatkan website edukasi adalah 0,001 (ada perbedaan bermakna). Nilai p untuk perbandingan perilaku defensive driving pada kelompok intervensi adalah 0,001 (ada perbedaan bermakna). Nilai p untuk perbandingan pengetahuan tentang defensive driving pada kelompok kontrol adalah 0,146 (tidak ada perbedaan bermakna). Nilai p untuk perbandingan perilaku defensive driving pada kelompok kontrol adalah 0,226 (tidak ada perbedaan bermakna). Terdapat perbedaan pengetahuan defensive driving (p = 0,001) dan perbedaan perilaku defensive driving (p = 0,001) antara kelompok intervensi dan kelompok kontrol. Selanjutnya disimpulkan bahwa website edukasi sukses dalam meningkatkan pengetahuan dan perilaku defensive driving head truck operators PT X Semarang.Kata kunci: website edukasi; defensive driving; pengetahuan; perilaku; operator head truck